(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2026)
Strategic human resource management (SHRM) has emerged among the most significant forces behind the performance of organizations since it integrates human capital to its business objectives to generate innovation, strength and competitive advantage. This paper has discussed the importance of new SHRM practices in enhancing performance in organisations by covering the issue of acquisition of talent, employee engagement, management of diversity and integration of technology in an organisation. Relying on the detailed examination of the secondary materials, such as scholarly sources, industry reports, and case studies, the paper addresses the major gaps of traditional HR practices, such as the inability to align with the strategic goals and the inadequate application of the data-oriented decision-making. The analysis shows that the barriers to SHRM adoption include resistance to change and lack of resources; it proposes useful action plans to overcome them. This book gives organizations a guideline on how they should use SHRM to reap the long term success in the dynamic global markets using theoretical models coupled with empirical data.